2008
DOI: 10.1177/1479972307086724
|View full text |Cite
|
Sign up to set email alerts
|

Different short-term and longitudinal results on perceived health status for asthma and COPD patients after pulmonary rehabilitation. Patients living alone have the largest improvements in perceived quality of life

Abstract: A combined sample (n = 132) of asthma (70%, n = 92) and chronic obstructive pulmonary disease (COPD) (30%, n = 40) patients was assessed for short-term and longitudinal changes in perceived health status (HS), quality of life (QoL), and trait anxiety after a 4-week inpatient pulmonary rehabilitation program (PRP). The total sample improved on HS (P = 0.009, effect size (ES) = 0.12) and QoL (P = 0.011, ES = 0.16) immediately after rehabilitation but improvements diminished at 6 months follow-up. Trait anxiety s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
1
17
1
2
Order By: Relevance
“…Six months afterwards, however, these improvements had faded with significant deterioration of HRQL, anxiety and depression. These findings are in line with Haave & Hyland (34), who found transient effect of a 4‐week inpatient rehabilitation programme on perceived quality of life and anxiety in patients with COPD as they had relapsed by the 6‐month follow‐up. Our findings may be attributed to the length of the rehabilitation programme, i.e.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Six months afterwards, however, these improvements had faded with significant deterioration of HRQL, anxiety and depression. These findings are in line with Haave & Hyland (34), who found transient effect of a 4‐week inpatient rehabilitation programme on perceived quality of life and anxiety in patients with COPD as they had relapsed by the 6‐month follow‐up. Our findings may be attributed to the length of the rehabilitation programme, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Further, follow‐up regimes, e.g. monthly follow‐up telephone calls and regular reinforcement visits, tend to produce better longitudinal results (34). In the present study, one centre offered telephone follow‐up talks after 3 weeks and two centres offered a 2‐week reinforcement visit 9 or 12 months after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, patients living with a partner or perceiving high satisfaction with available social support showed less hospital readmission rates, dyspnea, or depressive symptoms as well as improved exercise tolerance and survival rates compared to patients living alone or perceiving low satisfaction with social support [55, 56]. However, other studies failed to observe such associations or found patients living alone to show even greater improvements in quality of life after pulmonary rehabilitation [57, 58]. The specific mechanisms that might underlie possible associations between stronger social support and better COPD disease status remain to be investigated.…”
Section: Psychosocial Influences On Copdmentioning
confidence: 99%
“…However, Haave et al. (24) found that anxiety tended to increase after 6 months. Similarly, Griffiths et al.…”
Section: Introductionmentioning
confidence: 99%